2014
DOI: 10.1186/1471-2458-14-s3-s3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of cardiovascular disease risk factors among the residents of urban community housing projects in Malaysia

Abstract: Objectives: The objectives are to assess the prevalence and determinants of cardiovascular disease (CVD) risk factors among the residents of Community Housing Projects in metropolitan Kuala Lumpur, Malaysia. Method: By using simple random sampling, we selected and surveyed 833 households which comprised of 3,722 individuals. Out of the 2,360 adults, 50.5% participated in blood sampling and anthropometric measurement sessions. Uni and bivariate data analysis and multivariate binary logistic regression were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 41 publications
8
36
6
Order By: Relevance
“…[18][19][20] Studies carried out in China and USA showed that HNT is a predictor for the occurrence of higher TC values. 21,22 Own study confirmed that HTN is slightly more frequently diagnosed in women than in men; 23 however, many authors indicated that HTN is more common in men. [24][25][26][27][28] In Bosnia and Herzegovina and Brazil, approx.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…[18][19][20] Studies carried out in China and USA showed that HNT is a predictor for the occurrence of higher TC values. 21,22 Own study confirmed that HTN is slightly more frequently diagnosed in women than in men; 23 however, many authors indicated that HTN is more common in men. [24][25][26][27][28] In Bosnia and Herzegovina and Brazil, approx.…”
Section: Discussionsupporting
confidence: 59%
“…22 In the present study, the percentage was much lower, and gender did not affect significantly the number of people with diabetes, as was confirmed by the results of other authors. 24,25 In Malaysia and Lebanon, women were significantly more likely to develop DM; 23,36 however, other studies showed that men often had a significantly higher values of GL. 21,37 On examination day, the IFG (≥100 mg%) were diagnosed in 18.0% of women and 20.9% of men.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…11 In addition, some shocking findings from a study among low-income communities in urban Kuala Lumpur reported the prevalence of obesity, hypercholesterolemia, hypertension, and diabetes to be 54.8%, 51.5%, 39.3%, and 7.8%, respectively. 12 These survey findings underline the need to specifically improve efforts to prevent and control the burden of NCD among lowincome communities in urban Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…3 The social and economic implications of CVDs in terms of increased burden on the healthcare system, family sufferings, Disability Adjusted Life Years (DALYs) lost, reduced productivity and economic outputs are enormous and well documented. 4,5,6 Pakistan has been confronted with an increasing risk of cardiovascular diseases due to non-implementation of food safety laws, unhealthy dietary practices, poor sanitation and hygiene practices, population explosion, rapid urbanization, limited resources, lack of physical activity and unhealthy lifestyles. 7,8 Women share a greater burden of CVDs than men due to sedentary lifestyles, reproductive stress and poor dietary intake.…”
Section: Introductionmentioning
confidence: 99%